2008
DOI: 10.1016/j.bbabio.2008.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of the chlorophyll d containing photosystem I from the cyanobacterium, Acaryochloris marina

Abstract: Absorbance difference spectroscopy and redox titrations have been applied to investigate the properties of photosystem I from the chlorophyll d containing cyanobacterium Acaryochloris marina. At room temperature, the (P740(+)-P740) and (F(A/B)(-)-F(A/B)) absorbance difference spectra were recorded in the range between 300 and 1000 nm while at cryogenic temperatures, (P740(+)A(1)(-)-P740A(1)) and ((3)P740-P740) absorbance difference spectra have been measured. Spectroscopic and kinetic evidence is presented tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…However, experimental evidence for this interpretation was completely indirect. Moreover, it has been shown that the potential of P740 in A. marina is almost the same as that in Synechocystis (+435 mV) (6,13). The cytochrome b 6 f complexes are situated between the PS II and PS I complexes, although we have no data on the potential of these complexes in A. marina.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, experimental evidence for this interpretation was completely indirect. Moreover, it has been shown that the potential of P740 in A. marina is almost the same as that in Synechocystis (+435 mV) (6,13). The cytochrome b 6 f complexes are situated between the PS II and PS I complexes, although we have no data on the potential of these complexes in A. marina.…”
Section: Discussionmentioning
confidence: 45%
“…In PS I, the redox potential of P740 (corresponding to P700 for other oxygenic photosynthetic organisms) is the same as that of P700 (6,13), suggesting that no specific mechanism exists to compensate for the lower energy from the longer wavelength absorption of Chl d. Thus, one can conclude that the redox potentials of the special pair in oxygenic photosynthetic organisms are determined by the oxidizing side of the PS and not by the reducing side. These considerations suggest that a determining factor for the potential of the special pair with a specific pigment(s) might be related to an oxidation reaction that includes ligands and/or hydrogen bonds from the amino acid(s) of proteins to the pigments.…”
mentioning
confidence: 80%
“…Tomo et al 2007;Schenderlein et al 2008). This reflects in a loss of between 75 and 95 meV (3-4 k b T) in energy available for the photochemical reactions, which is intriguing from the evolutionary point of view (Hu et al 1998;Tomo et al 2007;Santabarbara et al 2007;Schlodder et al 2007;Schenderlein et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Though, chemically, Chl d is distinct from Chl a only for a formyl substitution at C 3 position of ring I of the tetra-pyrrol ring (Holt and Morley 1959), the energy of the lowest singlet excited state is redshifted by more than 30 nm in pigment solutions (Nieuwenburg et al 2003) and by 30-40 nm in the photosynthetic apparatus of A. marina (e.g. Tomo et al 2007;Schenderlein et al 2008). This reflects in a loss of between 75 and 95 meV (3-4 k b T) in energy available for the photochemical reactions, which is intriguing from the evolutionary point of view (Hu et al 1998;Tomo et al 2007;Santabarbara et al 2007;Schlodder et al 2007;Schenderlein et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation